Reportaż radiowy a pejzaż dźwiękowy. Zarys problematyki - Czarnek-Wnuk, Paulina (Zagadnienia Rodzajów Literackich, 2021)
The article is an attempt to enter scientific reflection relating to radio reportage in the field of sound studies, especially in one of its original elements — the theory of soundscape created by Raymond Murray Schafer in the 1960s. It starts with the basic terminological solutions in the field of soundscape and the audial form of reportage, then juxtaposes them with each other and indicates the possibilities of their mutual penetration in both scientific and media fields. It presents the common features of a radio documentary and a soundscape, e.g. focus on reality, attention to sound, specific narration, the use of the oral history method etc. This paper also shows the difference between these two forms such as a greater level of creativity in the case of reportage in combination with the “raw” naturalness of the soundscape. It also highlights how the idea of acoustic ecology can use radio reportage to disseminate its assumptions. Finally, it postulates the inclusion of this audio genre as an element of the soundscape to a harmonious hi-fi space and considers as justified to set together the experiences of both the discussed phenomena on theoretical as well as practical grounds, and to continue the reflection as sketched out in this article.